Two new species of blind, forest litter-inhabiting ground beetles from the subtribe Anillina (Carabidae: Trechinae: Bembidiini) from eastern U.S.A. - Sokolov, Igor M.; Carlton, Christopher E. (Zootaxa, 2008)
Two new species of anilline ground beetles are described from the Appalachian Mountains of eastern United States. The description of Serranillus septentrionis n. sp. is based on specimens collected in montane areas of western Virginia (37°25.33’N, 79°45.43’W). This species extends the range of the genus approximately 200 km north of its closest known congeners, S. dunavani (Jeannel) and S. jeanneli Barr, and differs from them mainly in characters of the male genitalia. A key is provided that will allow separation of these three species without dissection. The description of Anillinus cherokee n. sp. is based on specimens collected in Great Smoky Mountains National Park and nearby areas of Nantahala National Forest, western North Carolina (35°21.33’N, 83°56.05’W). The species is externally similar to A. loweae Sokolov and Carlton and A. steevesi Barr, and differs from those species in characters of the male genitalia.